COMPARATIVE ANALYSIS OF ATP6 MITOCHONDRIAL GENE DIVERSITY IN ARABIAN AND NON-ARABIAN HORSE BREEDS - M. M. M. Ahmed; A. Sheikh1; M. H. Z. Mutwakil; K. S.Saini; F. A.S. Alsulaimany; A. A EL Hanafy; J. S. M. Sabir (Journal of Animal and Plant Sciences, 2016)
Arabian horse breeds are famous for their strength, disease resistance and endurance. Originating from Arabian Peninsula, their progeny is considered among the best horse breeds of the world. Maternally inherited mitochondrial genome represents high genetic diversity in modern horse population. ATP6 gene of mt DNA from 46 horse samples of Middle Eastern Arabian, Western Arabian, mixed (hybrid) Arabians and non-Arabians were sequenced and analyzed to assess the genetic diversity and phylogenetic relationships among them. We have found nine haplotypes in our study. Totally, 99-nucleotide base substitutions were observed with seven variables, which accounted for six transitions and one transversion. Four single nucleotide polymorphismswereobserved in our study. Arabian horse breeds showed high diversity and shared many haplotypes among the population.The observed haplotype diversity and the average evolutionary divergence over all the sequence pairs were 0.8141 and 0.007 respectively.In addition, these datasets may also be useful for strain genotyping, data conservation, effective breeding and individual breed selection for desirable traits.
Keywords: Genetic Diversity; Mitochondrial DNA; ATP6 gene; Arabian horse